Borders, boundaries and bodies: The rise of overpopulation warriors - Turner, Bryan S. (Hagar: Studies in Society and Culture, 2006)
In traditional societies, there was a permanent and more or less functional relationship between the body, morality and political authority. The moral boundaries of the body were useful in defining the political borders of the state. This article examines these notions in a variety of political and sociological perspectives on power and authority. Although the relationship between body and politics continues today, there are major developments in the nature of human conflict, medical technology and the means of military violence that have brought about important changes in the conduct of war, where, for example, “camp rape” is used as a method of destroying whole societies. The article concludes by examining a new version of Malthusian demographic theory to consider the impact of new medical and military technology on the ancient connection between bodies, ethics and law. These global changes to the relationship between technology and the body, especially military technology, creates new possibilities of catastrophe, which have been explored most recently in the work, of Paul Virilio on speed in modern societies.